Pelaksanaan Perjanjian Kredit pada Koperasi Simpan Pinjam Kopdit Swasti Sari Kota Kupang - Romualdo Erlangga B Kosad Putra; Sukardan Aloysius; Agustinus Hedewata (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to analyze the implementation of credit agreements at the Kopdit Swasti Sari savings and loan cooperative in Kupang City. The writing of this research uses empirical legal methods. Types and sources of data are primary data, secondary data and tertiary data. Data techniques are conducted by interview, documentation and literature study. Data processing is done by Editing, and Coding. The results of this study are that the problems that arise in credit agreements at the Swasti Sari Savings and Loan Cooperative in Kupang City are bad debts, namely loans that have difficulty by the debtor to fulfill the obligations agreed upon between the creditor and the debtor due to deliberate or out of control factors. Problems regarding bad credit occur from the debtor or cooperative members who are late in fulfilling installments or do not pay their debts. The settlement procedure for defaults in credit agreements at the Swasti Sari Savings and Loan Cooperative is that if the debtor has income and there is a good intention to settle the loan, rescheduling can be carried out, if the debtor has income but does not have a good intention to settle the loan, confiscation of collateral can be carried out, if the debtor no longer has income but there is a good intention to settle the loan, it can be done by offering the sale of collateral, if the debtor no longer has income or there is no good intention to settle the loan, confiscation of collateral can be carried out and then sold.